Analisis Perbandingan Algoritma Longest Common Subsequence Dengan Simple Hill Climbing Pada Permainan TTS - Yardani Yardani (Graha Mitra Edukasi, 2022)
Crossword is a game to sharpen the brain. Crossword puzzles can be used in the field of education to test students' abilities, so that the questions used are adapted to their needs. But it will be difficult if a large number of questions are used, because to make a crossword puzzle from a set of questions, the possible combinations of existing words form a crossword puzzle. Research in optimizing the filling of empty spaces in the crossword matrix board certainly requires an algorithm using a comparison of the Longest Common Subsequence (LCS) algorithm and the Simple Hill Climbing algorithm. By comparing the performance of the Longest Common Subsequence (LCS) algorithm and the Simple Hill Climbing algorithm, it will be known how the work and performance in terms of speed and accuracy of the two algorithms work. The questions displayed in the crossword application are obtained from the database access randomly by the program. The crossword puzzle that is formed is a collection of answers to the questions used, the answers to the questions are arranged in such a way that they intersect with one another. On this matrix board, the answers to the questions will be placed to form a crossword puzzle. Each letter of the answer will occupy one cell on the matrix board. The number of questions is the number of questions that will be used in the crossword game. Apart from receiving input from the user, the application also provides output to the user in the form of a crossword puzzle and the correct answer from the TTS